Modification of Purple Sweet Potato Flour using Hydrogen Rich Water - Gita Indah Budiarti; Ika Dyah Kumalasari; Endah Sulistiawati; Mitha Ulli Rahmatillah; Qaulina Tsabit (Universitas Ahmad Dahlan, 2022)
The increasing need for wheat flour in Indonesia needs to be overcome by looking for alternatives to wheat flour. Wheat flour has the disadvantage of high sugar content, so flour from local tubers is needed, which is healthier, namely purple sweet potatoes. The disadvantage of local tubers if they are used as flour is their flourishing power so they need to be modified. Hydrogen rich water (HRW) is alkaline water that can be used to modify starch in purple sweet potato flour. The purpose of the study was to determine the effect of HRW modification on water content, swelling power, ash content and color. The method used is soaking using variable pH (5.9), soaking time (15, 30 minutes) and compared with citric acid 1% with soaking time 30 minutes. The optimal analysis results were obtained at pH 9, soaking time of 30 minutes using HRW with a moisture content of 6%, swelling power of 4.1 g/g, ash content of 10%, the fat content of 13.5%, color L, a, b respectively 65.34; -0.33; 16.03.